Obstructive sleep apnea syndrome and neuropsychological function in pediatric stroke. (March 2020) - Slim, Mahmoud; Westmacott, Robyn; Toutounji, Sandra; Singh, Jaspal; Narang, Indra; Weiss, Shelly; Krishnan, Pradeep; Grbac, Elena; Surmava, Ann-Marie; Andres, Kathleen; MacGregor, Daune; deVeber, Gabrielle; et al.
Abstract: Objectives: To assess the prevalence of obstructive sleep apnea syndrome (OSAS) in children with arterial ischemic stroke (AIS) and to evaluate its association with neuropsychological outcomes. Methods: We conducted a cross-sectional study of sleep health and neuropsychological outcome in children with AIS. A consecutive cohort of children attending a stroke clinic were assessed using a standardized pediatric sleep questionnaire (PSQ) and standardized measures of pediatric stroke outcome and intellectual, executive and adaptive function. High risk for OSAS was defined as PSQ score ≥0.33. Results: Overall, 102 children were included (55% males, median age: 9 years [interquartile-range [IQR]: 6–14]). The prevalence of OSAS in children with AIS was significantly higher compared to published normative prevalence rate (25.5% vs 5%, p < 0.001). Children with OSAS were more likely to have infarcts affecting both the anterior and posterior circulation (37.5% vs 9.5%, p = 0.021). In addition, children with OSAS had significantly higher median Pediatric Stroke Outcome Measure (PSOM) scores (2 [IQR: 0–2] vs 1 [IQR: 1–3.5], p = 0.01) and were more likely to be prescribed concomitant medications affecting sleep architecture (50% vs 22.4%, p = 0.007). OSAS was associated with significantly lower scores on intellectual, memory, cognitive, behavioral, attention, executive and adaptive function scales. The association between PSQ and intellectual ability and working memory remained statistically significant upon controlling for potential confounding factors including stroke related characteristics (neurologic impairment and arterial territory). Conclusions: The prevalence of OSAS in children with AIS compared to healthy controls is significantly elevated and is associated with poor neuropsychological outcomes. We highlight the importance of regular screening for OSAS – a modifiable risk factor - in children with AIS. The specific risk factors for OSAS and the potential benefits of therapeutic interventions in this patient population warrant further investigation. Highlights: Obstructive sleep apnea syndrome (OSAS) prevalence in childhood stroke is high. OSAS correlates significantly with poor neuropsychological function. Our study highlights the importance of screening for OSAS in children with stroke. Future studies should investigate therapeutic interventions for OSAS in stroke.